Promoting a Second-Tier Protection Regime for Innovation of Small and Medium-Sized Enterprises in South Asia : The Case of Sri Lanka - Punchi Hewage, Nishantha Sampath (Nomos Verlagsgesellschaft mbH & Co. KG, 2015)
Intellectual Property law is a dynamic field; its ever-changing landscape challenges us to constantly revisit the existing laws and policies. Although ideological currents of a second-tier patent (STP) regime are sweeping through the South Asian region in recent years, the concept of utility model or petty patent remains a largely unexplored option in Sri Lanka and in other parts of the South Asian region. Against this backdrop, this book offers an alternative approach to incentivise minor and incremental innovations of SMEs. It also explores whether Sri Lanka and other developing economies in the South Asian region can benefit from such an STP regime if it is tailored to the specific characteristics of the innovation landscape of the country.
English
Keywords: Second-Tier-Patent; Markenrecht; Urheberrecht / Gewerblicher Rechtsschutz und Medienrecht; Sri Lanka; Gewerblicher Rechtsschutz; Gebrauchsmusters